Best Practices in Call Centre’s Communication Skills - Qin, Wanhui (2013)
Call centre functions as an interface between customers and organization. It handles high volume of calls, placed and received for the purpose of customer service, marketing, sales, telemarketing, technical support or other specialized business activity (Dawson, 1997). Prabhaker et al. (1997) identified the necessity for organizations to provide a superior service on the purpose of ensuring business survival in a service sector economy. Call centre provides customers faster, cheaper and more effective and convenient contact with organizations. Call centre agents play an increasingly significant role in the linkage between organizations and customers. For example, bank’s payment reminders provide customers with such services as reminding of the upcoming or late payments while at the same time offering options to pay so as to avoid late charges. It is necessary for employees working in call centre of payment recovery. In reality, not all call centres are successful in persuading customers to settle their credit in time. Therefore, to uncover the best practice in call centre’s communication skills, Osgood & Schramm’s Circular Model is applied in this research. To explore the best practice in call centre’s communication skills, the author interviews 15 call centres in the Klang Valley. The interview is semi-structured with 8 open questions. Thematic analysis is used to analyze the interview texts in order to achieve research objectives.